Differential effect of LPS and paclitaxel on microglial functional phenotypes and circulating cytokines: the possible role of CX3CR1 and IL-4/10 in blocking persistent inflammation - Ha, Joong-Won; You, Min-Jung; Park, Hyun-Sun; Kim, Jong Wan; Kwon, Min-Soo (Archives of pharmacal research, 2019)
Neuroinflammation plays a role in cancer chemotherapy-induced chronic pain. Thus far, most studies have focused on neuroinflammation suppression. However, there are limited reports of which factor is involved in the transition from acute inflammation to chronic inflammation, resulting in neuroinflammation and chronic pain. Here, we compared the inflammatory reaction and pain response induced by LPS and paclitaxel. LPS (0.5 mg/kg) or paclitaxel (2 mg/kg/day for 5 days) was administered intraperitoneally to mice, and mechanical allodynia was examined by von Frey test. LPS induced transient mechanical allodynia, whereas paclitaxel induced persistent mechanical allodynia. The CD86/CX3CR1 ratio remained unchanged due to CX3CR1 elevation following LPS injection, whereas the ratio was increased on day 1 after paclitaxel injection. LPS also increased CD45, CCL2, and CCL5 mRNA in the spinal cord and circulating pro- and anti-inflammatory cytokines 1 day after injection; however, the pattern was not consistent. Paclitaxel gradually increased inflammatory cytokines in the spinal cord. CX3CR1 might be involved in blocking the transition from acute pain to persistent pain in the LPS group. In addition, serum IL-4 and IL-10 elevation in the LPS group may be associated with chronic pain prevention. Therefore, targeting CX3CR1, IL-4, and IL-10 might be an alternative therapeutic strategy.